Mechanism of action of novel synthetic dodecapeptides against Candida albicans - Maurya, Indresh Kumar; Thota, Chaitanya Kumar; Sharma, Jyotsna; Tupe, Santosh Genba; Chaudhary, Preeti; Singh, Manoj Kumar; Thakur, Indu Shekhar; Deshpande, Mukund V.; Prasad, Rajendra; Chauhan, Virander Singh (Biochimica Et Biophysica Acta-General Subjects, 2013)
Background: Three de novo designed low molecular weight cationic peptides (IJ2, IJ3 and IJ4) containing an unnatural amino acid alpha,beta-didehydrophenylalanine (APhe) exhibited potent antifungal activity against fluconazole (FLC) sensitive and resistant clinical isolates of Candida albicans as well as non-albi cans and other yeast and filamentous pathogenic fungi. In the present study, their synthesis, susceptibility of different fungi and the mechanism of anti-candidal action have been elucidated. Methods: The antimicrobial peptides (AMPs) were synthesized by solid-phase method and checked for antifungal activity against different yeasts and fungi by broth microdilution method. Anti-candidal mode of action of the peptides was investigated through detecting membrane permeabilization by confocal microscopy, Reactive Oxygen Species (ROS) generation by fluorometry, apoptosis and necrosis by flow cytometry and cell wall damage using Scanning and Transmission Electron Microscopy. Results and conclusions: The MIC of the peptides against C. albicans and other yeast and filamentous fungal pathogens ranged between 3.91 and 250 mu M. All three peptides exhibited effect on multiple targets in C. albi cans including disruption of cell wall structures, compromised cell membrane permeability leading to their enhanced entry into the cells, accumulation of ROS and induction of apoptosis. The peptides also showed synergistic effect when used in combination with fluconazole (FLC) and caspofungin (CAS) against C. albi cans. General significance: The study suggests that the AMPs alone or in combination with conventional antifungals hold promise for the control of fungal pathogens, and need to be further explored for treatment of fungal infections. (C) 2013 Elsevier By. All rights reserved.
Keywords: Antifungal peptide; Antimicrobial peptide (AMP); Apoptosis; Candida albicans; Reactive Oxygen Species (ROS)

Molecular studies of NAD- and NADP-glutamate dehydrogenases decipher the conundrum of yeast-hypha dimorphism in zygomycete Benjaminiella poitrasii - Pathan, Ejaj K.; Ghormade, Vandana; Panwar, Sneh Lata; Prasad, Rajendra; Deshpande, Mukund V. (Fems Yeast Research, 2019)
Benjaminiella poitrasii, a zygomycete, shows glucose- and temperature-dependent yeast (Y)-hypha (H) dimorphic transition. Earlier, we reported the biochemical correlation of relative proportion of NAD- and NADP-glutamate dehydrogenases (GDHs) with Y-H transition. Further, we observed the presence of one NAD-GDH and two form-specific NADP-GDH isoenzymes in B. poitrasii. However, molecular studies are necessary to elucidate the explicit role of GDHs in regulating Y-H reversible transition. Here, we report the isolation and characterization of one NAD (BpNADGDH, 2.643 kb) and two separate genes, BpNADPGDH I (Y-form specific, 1.365 kb) and BpNADPGDH II (H-form specific, 1.368 kb) coding for NADP-GDH isoenzymes in B. poitrasii. The transcriptional profiling during Y-H transition showed higher BpNADPGDH I expression in Y cells while expression of BpNADPGDH II was higher in H cells. Moreover, the yeast-form monomorphic mutant (Y-5) did not show BpNADPGDH II expression under normal dimorphism triggering conditions. Transformation with H-form specific BpNADPGDH II induced the germ tube formation in Y-5, which confirmed the cause-effect relationship between BpNADPGDH genes and morphological outcome in B. poitrasii. Interestingly, expression of H-form specific BpNADPGDH II also induced germ tube formation in human pathogenic, non-dimorphic yeast Candida glabrata, which further corroborated our findings.
Keywords: Benjaminiella poitrasii; Candida glabrata; differential gene expression; dimorphism; monomorphic mutant; NAD/NADP-glutamate dehydrogenase; yeast-hypha transition